2015
DOI: 10.1371/journal.pntd.0003413
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Sub-microscopic P. vivax Infections: Prevalence and Determining Factors

Abstract: BackgroundSub-microscopic (SM) Plasmodium infections represent transmission reservoirs that could jeopardise malaria elimination goals. A better understanding of the epidemiology of these infections and factors contributing to their occurrence will inform effective elimination strategies. While the epidemiology of SM P. falciparum infections has been documented, that of SM P. vivax infections has not been summarised. The objective of this study is to address this deficiency.Methodology/Principal FindingsA syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
142
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(149 citation statements)
references
References 56 publications
7
142
0
Order By: Relevance
“…30 The contrasting complexity of infection for the two species is comparable to previous reports from the PNG north coast 39,68 and demonstrates that this pattern is also observed across areas with widely varying endemicity including areas with low parasite prevalence. 30 This may be in part due to lower transmission areas having increasing proportions of imported infections, which reflects the MOI and diversity of the infection origin, 22,69,70 and this effect would be enhanced for P. vivax by the fact that relapse can occur 1-3 years after the primary infection. 71 The high complexity of infection for P. vivax regardless of parasite prevalence is also comparable to other studies where high infection complexity and diversity were found even with sustained low parasite prevalence such as in South America 33,72,73 and Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…30 The contrasting complexity of infection for the two species is comparable to previous reports from the PNG north coast 39,68 and demonstrates that this pattern is also observed across areas with widely varying endemicity including areas with low parasite prevalence. 30 This may be in part due to lower transmission areas having increasing proportions of imported infections, which reflects the MOI and diversity of the infection origin, 22,69,70 and this effect would be enhanced for P. vivax by the fact that relapse can occur 1-3 years after the primary infection. 71 The high complexity of infection for P. vivax regardless of parasite prevalence is also comparable to other studies where high infection complexity and diversity were found even with sustained low parasite prevalence such as in South America 33,72,73 and Sri Lanka.…”
Section: Discussionmentioning
confidence: 99%
“…12 At low transmission, the strong LD could be explained by relapse because in the absence of a high rate of new infections containing distinct clones, there would be frequent recombination between meiotic siblings (inbreeding) and the maintenance of multiple non-recombining lineages. Furthermore, the longer relapse rates in P. vivax strains from temperate versus the shorter relapse rates of strains from tropical climates 4 has likely contributed to the complex patterns observed. The hypnozoite is therefore likely to play a major role in shaping P. vivax population structure.…”
Section: Impact Of Plasmodium Vivax Biology On Transmission Dynamicsmentioning
confidence: 99%
“…Since the advancement of sensitive molecular diagnostics, it has been recognised that a significant proportion of the P. vivax burden is composed of low-density, asymptomatic infections that remain undetected by standard epidemiological tools (reviewed by Ref. 4 ) and that these proportions may increase with decreasing transmission. 5 Genotyping approaches that distinguish between different parasite clones within an infection to estimate the multiplicity of infection (MOI) have provided some insight into the intensity of transmission in different endemic areas.…”
Section: Introductionmentioning
confidence: 99%
“…At all levels of transmission, asymptomatic and sub-microscopic P. vivax infections are very common [10]. Most if not all of these infections produce gametocytes [11] and likely contribute substantially to maintaining P. vivax transmission [12].…”
Section: Introduction -Why a Vaccine For Plasmodium Vivax Is Neededmentioning
confidence: 99%